2016
DOI: 10.18632/oncotarget.11586
|View full text |Cite
|
Sign up to set email alerts
|

Expression and regulation of immune-modulatory enzyme indoleamine 2,3-dioxygenase (IDO) by human airway epithelial cells and its effect on T cell activation

Abstract: Indoleamine 2,3-dioxygenase (IDO) catalyzes the degradation of tryptophan, which plays a critical role in immune suppression through regulating the production of a series of metabolites that are generally referred to as kynurenines. It has become increasingly clear that epithelial cells (ECs) play an active role in maintaining lung homeostasis by modulating the function of immune cells via producing cytokines, chemokines, and anti-microbial mediators. In this study we assessed the regulation of IDO activity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 64 publications
1
40
0
Order By: Relevance
“…Indoleamine 2,3‐dioxygenase 1 is a rate‐limiting enzyme in the catabolism of the essential amino acid tryptophan along the kynurenine pathway, and it is widely distributed in various types of tumors . Broad evidence has indicated that local tryptophan deprivation and the accumulation of kynurenines produced by IDO1 elevation crucially facilitate the escape of malignant tumors from host immune killing with multiple effects, including the suppression of T and NK cells, the generation and activation of regulatory T cells and myeloid‐derived suppressor cells, and the promotion of tumor angiogenesis …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indoleamine 2,3‐dioxygenase 1 is a rate‐limiting enzyme in the catabolism of the essential amino acid tryptophan along the kynurenine pathway, and it is widely distributed in various types of tumors . Broad evidence has indicated that local tryptophan deprivation and the accumulation of kynurenines produced by IDO1 elevation crucially facilitate the escape of malignant tumors from host immune killing with multiple effects, including the suppression of T and NK cells, the generation and activation of regulatory T cells and myeloid‐derived suppressor cells, and the promotion of tumor angiogenesis …”
Section: Introductionmentioning
confidence: 99%
“…8,9 Broad evidence has indicated that local tryptophan deprivation and the accumulation of kynurenines produced by IDO1 elevation crucially facilitate the escape of malignant tumors from host immune killing with multiple effects, including the suppression of T and NK cells, the generation and activation of regulatory T cells and myeloid-derived suppressor cells, and the promotion of tumor angiogenesis. [10][11][12][13][14][15] As an immune escape mechanism, high constitutive IDO1 expression, driven by intrinsic cellular changes such as gene mutations associated with carcinogenesis, represents an adverse prognostic factor in colorectal cancer, endometrial cancer, ovarian carcinoma, and a number of other cancers. [16][17][18][19][20] In contrast, in breast carcinoma, early stage cervical cancer, and melanoma, IDO1 expression is accompany the host antitumor immune response, and it tends to positively correlate with survival.…”
Section: Introductionmentioning
confidence: 99%
“…It has become widely clear that epithelial cells as a first line of defense mechanism can play a crucial role in modulating the function of immune cells through production of cytokines and other mediators, which ultimately maintain immune homeostasis [45]. Although epithelial cells modulate immune responses via their own ability to produce a plethora of cytokines in vivo, not all cell lines produce constitutive amounts of cytokines in vitro [16,[45][46][47]. In vivo assays have shown that highly elevated levels of the inflammatory cytokine TNF-α and the anti-inflammatory cytokine IL-10 are detected in ovarian cancer [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the immunosuppressive effects of IDO, it has been shown that epithelial cells can suppress antigen‐specific and antigen‐non‐specific T cell activation (i.e., T cell proliferation and IFN‐γ production) through IDO activity . The immunomodulatory activity of IDO has been shown to affect immune responses associated with hRSV .…”
Section: Hrsv‐infection and Ido Activitymentioning
confidence: 99%
“…Further, the authors showed that the induction of IDO activity was dependent on virus infection and replication . Interestingly, T cell activation was partially recovered when TLR signaling was activated in epithelial cells after the addition of LPS and poly I:C, mimicking bacterial and viral infections, respectively . To date, the immunosuppressive effect of IDO induced by hRSV has only been demonstrated in vitro.…”
Section: Hrsv‐infection and Ido Activitymentioning
confidence: 99%